The Role of Technology in Fostering Innovation and Growth in Start-up Businesses - Khuan, Hendri; Andriani , Eva; Rukmana, Arief Yanto (West Science Journal Economic and Entrepreneurship, 2023)
The integration of technology within the context of start-up enterprises has emerged as a transformative force driving innovation and growth. This paper presents a bibliometric analysis of the literature on the role of technology in propelling business innovation and growth in start-ups. Through a systematic review of scholarly articles, this study aims to uncover key trends, themes, and influential contributions in the field. The analysis employs co-citation networks, author and institution mapping, journal analysis, and keyword clustering to map the intellectual landscape of this dynamic research domain. The findings highlight the centrality of concepts such as open innovation, digital transformation, and disruptive innovation, underscoring the multidimensional interplay between technology and start-up success. Prolific authors and influential institutions are identified, showcasing the collaborative nature of research in this area. The prominence of specific journals underscores the dissemination of knowledge within the academic community. The comprehensive keyword analysis reveals prevalent themes such as business models, performance, and open innovation, as well as emerging considerations including sustainability and barriers. The insights derived from this bibliometric analysis contribute to a deeper understanding of the complex dynamics that shape the symbiotic relationship between technology, innovation, and growth in start-ups.